2017
DOI: 10.1038/srep42271
|View full text |Cite
|
Sign up to set email alerts
|

AlkB homolog 3-mediated tRNA demethylation promotes protein synthesis in cancer cells

Abstract: The mammalian AlkB homolog (ALKBH) family of proteins possess a 2-oxoglutarate- and Fe(II)-dependent oxygenase domain. A similar domain in the Escherichia coli AlkB protein catalyzes the oxidative demethylation of 1-methyladenine (1-meA) and 3-methylcytosine (3-meC) in both DNA and RNA. AlkB homolog 3 (ALKBH3) was also shown to demethylate 1-meA and 3-meC (induced in single-stranded DNA and RNA by a methylating agent) to reverse the methylation damage and retain the integrity of the DNA/RNA. We previously repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
159
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(173 citation statements)
references
References 34 publications
4
159
0
1
Order By: Relevance
“…The demethylation of tRNA by recombinant ALKBH3 promotes tumor progression by significantly enhancing protein translation efficiency. 10 Consistent with the previous reports, our results also showed that ALKBH3 expresses demethylase activity for 1-meA, 3-meC, and N6-meA in total RNA of ALKBH3 knockdown or ALKBH3-overexpressed HCC cells. In this study, we found that ALKBH3 may regulate cell proliferation by affecting the cell cycle.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The demethylation of tRNA by recombinant ALKBH3 promotes tumor progression by significantly enhancing protein translation efficiency. 10 Consistent with the previous reports, our results also showed that ALKBH3 expresses demethylase activity for 1-meA, 3-meC, and N6-meA in total RNA of ALKBH3 knockdown or ALKBH3-overexpressed HCC cells. In this study, we found that ALKBH3 may regulate cell proliferation by affecting the cell cycle.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, ALKBH3 expresses demethylation activity against N6‐meA in tRNA within endogenously methylated RNA bases. The demethylation of tRNA by recombinant ALKBH3 promotes tumor progression by significantly enhancing protein translation efficiency . Consistent with the previous reports, our results also showed that ALKBH3 expresses demethylase activity for 1‐meA, 3‐meC, and N6‐meA in total RNA of ALKBH3 knockdown or ALKBH3‐overexpressed HCC cells.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…ALKBH1 is responsible for the demethylation of m 1 A58 in the TΨC-loop of tRNA; it regulates translational initiation by adjusting the levels of tRNA i Met , as well as translational elongation through adjusting the affinity of a dozen tRNA species to the elongation factor eEF1A. The related demethylase ALKBH3 (Ougland et al, 2004; Ueda et al, 2017) has also been characterized, although the cellular targets of ALKBH3 are still under investigation. With the first identified tRNA demethylases, the field has opened to the discovery that more demodification enzymes may exist to regulate modification status in response to cellular signaling or stress in order to reprogram tRNA stability and translation.…”
Section: Modifications In Abundant Noncoding Rnasmentioning
confidence: 99%
“…Recently, Ueda et al. have reported that m 6 A was also a substrate of ALKBH3 16. Interestingly, ALKBH3 shows a special substrate preference for RNA, targeting only m 6 A in tRNA, rather than those in mRNA or rRNA.…”
Section: The Discovery Of M6a and Its Functionmentioning
confidence: 99%